Application Of The Utmost Good Faith Principle In Life Insurance Business Management In Indonesia - Ashri Maunah, Nur; Sunargo, Bambang; Puspitaloka Mahadewi, Erlina (Publisher Cv. Inara, 2023)
The study focused on the purpose of this writing is to find out the application of the principle of utmost good faith in life insurance. The research method used in this study is to use data collection methods in library research or library research. In this literature study the author obtains the materials and library materials needed by studying books, writings, journal citations and statutory and legal products that are related to the subject matter according to topics in Indonesia so that it can be concluded that: first, legal principles in insurance coverage include insurable interest, utmost good faith, indemnity principle, subrogation principle, causaliteit principle, contribution principle, cause principle, follow of fortune. Second, the types of risk in insurance are pure and speculative risk, diversifiable and non-diversifiable risk, company risk, systemic risk, financial and non-financial risk, individual and group risk, static and dynamic risk. Third, the application of the principle of utmost good faith in life insurance is very important, because if there is submission of information and information that is incorrect, it can result in the insurance agreement being cancelle.